Penggunaan Kulit Buah Jeruk Manis (Citrus aurantium L.) Sebagai Pelapis Alami Untuk Mempertahankan Mutu Buah Cabai Merah (Capsicum annuum L.) Dan Ketahanan Terhadap Jamur Colletotrichum sp. - Indira Putri, Aviva; Wahyuningsih, Sri; Yulianty; Mahfut (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Red chili (Capsicum annuum L.) is an important horticultural crop that is widely used as a cooking spice. However, this fruit has a short shelf life and is susceptible to Colletotrichum sp. infection which causes anthracnose disease. One effort to extend the shelf life and suppress fungal infection is the use of natural coatings. Sweet orange peel(Citrus aurantium L.) which contains pectin has the potential to be used as a base material for natural coatings to increase the resistance of red chili. This study aims to determine the effect and determine the effective concentration of natural coatings from sweet orange peel on the quality of red chili and its resistance to Colletotrichum sp. The study used a Completely Randomized Design (CRD) with six treatment concentrations: 0%, 1%, 2%, 3%, 4%, and 5%, each repeated four times. The parameters observed included texture, weight loss, incubation period, disease incidence, disease severity, and number of conidia. The results showed that a concentration of 5% gave the best results in maintaining fruit texture and weight, extending the incubation period, and inhibiting disease development and reducing the number of Colletotrichum sp. conidia.